Mechanical properties of Portland cement concrete mixed with different doses of recycled brick powder and steel fiber - Mohammad Mohtasham Moein; Ali Mohtasham Moein; Ashkan Saradar; Sam E. Rigby; Hassan Tazari; Moses Karakouzian (Heliyon)
This research investigates the mechanical properties of Portland Cement Concrete (PCC), incorporating recycled brick powder (RBP) and steel fibers and addressing sustainability and performance enhancement in concrete materials. The experimental design systematically varied RBP content (0–15 %) and incorporated crimped steel fibers of two lengths (20 and 50 mm) at dosages of 0 %, 0.5 %, and 1 %. The rationale for these percentages stems from balancing material recycling potential with maintaining concrete structural integrity, with RBP serving as a partial cement replacement to reduce environmental impact and material waste. Comprehensive testing encompassed compressive strength, flexural strength, tensile strength, and impact resistance. Due to the high variability of impact data, a two-parameter Weibull distribution was applied to provide a more robust statistical interpretation of the results. The findings revealed that 5 % RBP in plain concrete caused slight reductions in mechanical properties, with decreases of 1.48 % in compressive, 1.12 % in flexural, 1.42 % in tensile, 3.19 % in first crack, and 3.03 % in failure strengths. Steel fiber incorporation significantly enhanced the concrete's response to static and short-term dynamic loading. The combination of lengths (20-mm and 50-mm steel fibers) demonstrated the greatest impact resistance, offering potential applications in infrastructure elements requiring improved durability, such as bridge decks, industrial flooring, and earthquake-resistant structures. While steel fibers substantially improved fatigue resistance under repeated impact loading, the addition of RBP was observed to partially mitigate these benefits. The impact test data for all mixtures were effectively characterized by the two-parameter Weibull distribution, with R2 values consistently exceeding 0.88, providing a reliable statistical framework for assessing concrete performance. The study contributes to sustainable construction practices by demonstrating a viable approach to incorporating recycled materials without substantially compromising mechanical properties.